2019
DOI: 10.1038/s41598-019-56174-8
|View full text |Cite
|
Sign up to set email alerts
|

Metabolomic and metallomic profile differences between Veterans and Civilians with Pulmonary Sarcoidosis

Abstract: Sarcoidosis is a disorder characterized by granulomatous inflammation of unclear etiology. In this study we evaluated whether veterans with sarcoidosis exhibited different plasma metabolomic and metallomic profiles compared with civilians with sarcoidosis. A case control study was performed on veteran and civilian patients with confirmed sarcoidosis. Proton nuclear magnetic resonance spectroscopy (1H NMR), hydrophilic interaction liquid chromatography mass spectrometry (HILIC-MS) and inductively coupled plasma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 57 publications
0
9
0
Order By: Relevance
“…1 H nuclear magnetic resonance (NMR)-based metabolomic analysis identified metabolites and metabolic pathways that can discriminate sarcoidosis patients from healthy ones. Acetoacetate, 3-hydroxybutyrate, carnitine, cystine, and trimethylamine N-oxide levels are significantly increased in sarcoidosis, with dysregulation of ketone bodies and citric cycle metabolism also being identified as hallmarks of this disease [173,174].…”
Section: Biomarkers For Sarcoidosismentioning
confidence: 99%
“…1 H nuclear magnetic resonance (NMR)-based metabolomic analysis identified metabolites and metabolic pathways that can discriminate sarcoidosis patients from healthy ones. Acetoacetate, 3-hydroxybutyrate, carnitine, cystine, and trimethylamine N-oxide levels are significantly increased in sarcoidosis, with dysregulation of ketone bodies and citric cycle metabolism also being identified as hallmarks of this disease [173,174].…”
Section: Biomarkers For Sarcoidosismentioning
confidence: 99%
“…Besides genetic variants and epigenetics, also metabolomics and biochemical pathways may differ among sarcoidosis patients with possible different antigenic triggers. In a study of Banoei et al, [43] a…”
Section: Metabolomicsmentioning
confidence: 95%
“…Military veterans are exposed to several inorganic materials including gun smoke, jet fuel, asbestos, lead, and dust storms which can be accompanied by the presence of silica, aluminum, and trace elements, including zirconium, strontium, and rubidium. The authors observed that metabolomic and metallomic profiles indeed differed between the two sarcoidosis groups, suggesting that pathophysiological mechanisms and pathways differ among sarcoidosis patients with different agents triggering the disease [43].…”
Section: Lessons Learned From Chronic Beryllium Disease and Silicosismentioning
confidence: 99%
See 1 more Smart Citation
“…Here, the sample size was calculated with the prevalence of NIHL in the factory (p = 0.20), the odds ratio of noise exposure in different groups (1.2), the type I error (ɑ = 0.05) and the type II error (ß = 0.20), and the case/control ratio (1:1). For the determination of the sample size, we also referred to the designs of similar studies (Banoei et al, 2019;Wang et al, 2020;Rothman et al, 2021). All workers were required to receive health examinations and hearing tests every 6 months.…”
Section: Subjects Sample Preparation and Metabolite Identificationmentioning
confidence: 99%